Nietzsche on the Diachronic Will and the Problem of Morality. (15th August 2012) - Tanesini, Alessandra
Abstract In this paper I offer an innovative interpretation of Nietzsche's metaethical theory of value which shows him to be a kind of constitutivist. For Nietzsche, I argue, valuing is a conative attitude which institutes values, rather than tracking what is independently of value. What is characteristic of those acts of willing which institute values is that they are owned or authored. Nietzsche makes this point using the vocabulary of self‐mastery. One crucial feature of those who have achieved this feat, and have consequently become agents, is that they possess a diachronic or long will and are consequently capable of the rational governance of future behaviour. The possession of a will of this sort is crucial because it is a necessary condition for engaging in temporally unified activities which are a requisite of authorship. Nietzsche, I argue, makes these points in his doctrine of eternal recurrence which provides a test that acts of will must pass to count as laws. In the final section of the paper I argue for the superiority of this interpretation over some of its competitors.